A Case of Traumatic Abdominal Wall Hernia with Shock Treated by Primary Closure of the Laparotomy Wound and Hernia Orifice - Takagi, Toru; Suzuki, Shohachi; Uno, Akihiro; Matsumoto, Keigo; Ochiai, Hideto; Ishikawa, Nozomu; Kawabata, Toshiki; Jindou, Osamu; Inaba, Keisuke (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2019)
A 48-year-old man was transferred to our emergency department with shock after sustaining injuries in a car collision accident. Abdominal CT performed after ensuring hemodynamic stability revealed traumatic abdominal wall hernia and emergency operation was performed. Intraoperative exploration revealed strangulation of a segment of the small intestine and mesentery. After ligation to control the bleeding and resection of the strangulated segment of the small intestine, the abdominal wall was closed directly. On day 5 after the operation, the patient developed delayed perforation of the ascending colon, and reoperation was performed. Thereafter, until the present, 14 months after the operation, the patient has shown no evidence of recurrence of the abdominal wall hernia. Direct closure is suitable for cases undergoing emergency repair of traumatic abdominal wall hernia, because of the possibility of delayed organ injuries.